Hypertension status among the adult population in a rural community of Keraniganj Upazila, Dhaka, Bangladesh - Farhana, A; Shakil, M; Khan, BU; Laskar, MS; Alam, M (Mediscope, 2018)
Hypertension or high blood pressure is a growing public health concern among the Bangladeshi adult population. The objective of this cross-sectional descriptive type of study was to estimate the proportion of hypertension in an adult population of Keraniganj Upazila, Dhaka. The sample size was 199 selected purposively. Among them, 53.8% were female, 82.4% Muslims. Of the total respondents, 15.6% were hypertensive and highest proportion (29.0%) of hypertensive patients was found in the age group of ≥50-<60 years. The study revealed that people who took extra fatty food for 3-5 days per week, people who took extra salt in their food, respondents had a positive family history of hypertension or diabetes mellitus were more prone to develop hypertension. The study also revealed that smokers were in higher risk of development of hypertension than the non-smokers were and the rate of hypertension was 36.8% among those having higher waist circumference within 100 cm - 109 cm than those having lower waist circumference within 60 cm - 69 cm. Newly identified hypertensive cases were 7.0% of the study population. Results of this study have profound implications for hypertension prevention programs in the rural community, pointing out the need for increased focus in addressing hypertension along with its all background causes. Mediscope Vol. 5, No. 2: Jul 2018, Page 21-29